Caracterización de Residuos Sólidos Urbanos de la Ciudad de Macas - Lucero Marca, Manuel Elías (2023)
Valencia and Sánchez (2016) state that "The production or generation of residual waste is a variable that depends on cultural factors such as the size of the population, the predominant socioeconomic activity, the educational level and the environmental awareness that people have". This research work aims to create data that will serve as the foundation for the development of environmental programs, encouraging education and environmental awareness, the physical characterisation of household solid trash in Macas city and the people who generate it. To physically describe home solid waste, two phases were used. Phase 1: General characterization of the urban population in Macas city through the initial application of a survey by Arellano, Gavilanes, and Gonzáles (2013) using the "Method of Urban Characterization and Socioeconomic Characterization" same that will enable knowing the per capita production (PPC) of solid waste. Phase 2: The solid trash generated by residents of the city was classified using statistical analysis. The procedure involved keeping track of how much solid waste the household produced for eight days, classifying and weighing it in accordance with its physical composition, and then calculating the sample size and producing data on per capita production, loose density, components, among other tasks that are covered in this report.